2013
DOI: 10.1590/s1414-462x2013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida e evolução leucêmica de portadores de síndromes mielodisplásicas

Abstract: Cad. Saúde Colet., 2013, Rio de Janeiro, 21 (2): 154-9 154 Artigo Original ResumoAs síndromes mielodisplásicas constituem um grupo de doenças de ordem clonal hematopoética evidenciadas por estudos em todo o mundo. A estimativa de sobrevida dos pacientes e de casos que apresentam evolução leucêmica requer investigação na população brasileira, pois não se conta com nenhum dado dessa natureza. Assim, este estudo objetivou caracterizar e estimar a sobrevida e evolução leucêmica de portadores de síndromes mielodisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…A study with the purpose of drawing the sociodemographic and clinical profile of MDS patients found that among the 29 selected patients, there was a predominance of the elderly group. The youngest patient of the sample was 22 years old, corroborating with the findings that report MDS as rare in pediatric patients …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study with the purpose of drawing the sociodemographic and clinical profile of MDS patients found that among the 29 selected patients, there was a predominance of the elderly group. The youngest patient of the sample was 22 years old, corroborating with the findings that report MDS as rare in pediatric patients …”
Section: Discussionsupporting
confidence: 89%
“…The youngest patient of the sample was 22 years old, corroborating with the findings that report MDS as rare in pediatric patients. 11 Pediatric MDS normally presents a more aggressive behavior, with more than 40% transformation for AML, but its pathogenesis is still poorly understood, since there is participation of a complex of anormal events. 4 In children, MDS is often seen in association with genetic disorders and inherited BM failure syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 54% of the patients in the present study reported not being married or in a consensual union; data which are similar to those found in studies conducted in Brazil and abroad. 5,[17][18][19] Family support is essential for patients who undergo HSCT, since they need to feel secure in the early stages of treatment and especially during hospitalization, and to be sure that they are not alone in this delicate moment of their lives.…”
Section: Discussionmentioning
confidence: 99%